A dynamic framework for strengthening women's social capital: strategies for community development in rural Bangladesh. (10th April 2017) - Seferiadis, Anastasia A; Cummings, Sarah; Maas, Jeroen; Bunders, Joske F G; Zweekhorst, Marjolein B M
Abstract: There is considerable evidence in the literature that social capital contributes to poverty alleviation, but evidence of how development actors can strengthen the productive social capital for poor people remains scarce. This article describes strategies to strengthen social capital developed by an NGO and poor women as part of a development programme, undertaken in Jessore District, rural Bangladesh, during 2006–2012. The NGO and the women leveraged bonding (familial), bridging (peers), and linking (vertical links to powerholders) social capital to improve the livelihoods of women and their families, simultaneously changing gender relations within households and communities. Against a background of local norms and ethics, the NGO and the women employed strategies that created opportunities for women to meet and exchange, and develop their social skills, know-how, self-worth and capacity to act. Drawing on these strategies, the article presents a dynamic framework for strengthening social capital for community development, providing theoretical insights into the mechanisms for doing so.